2017
DOI: 10.1155/2017/2790198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hole Perpendicularity Error on Mechanical Performance of Single-Lap Double-Bolt Composite Joints

Abstract: Static tensile experiments and numerical simulations were carried out to study effects of hole perpendicularity error on mechanical performance of single-lap double-bolt composite joints. Hole tilting angle, varying from 1 to 4 degrees, and hole tilting direction to account for anisotropic properties of composite material were investigated. Progressive damage model (PDM) based on Chang-Lessard type criterion with an extension by Olmedo was created, which involved seven failure modes and made material propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In drilling, perpendicularity is the deviation of the hole axis from the ideal cylinder axis with respect to the specified reference point. This geometrical defect reduces the load-bearing capacity of bolted joints causing stress concentration around hole edges [97,98]. The results show perpendicularity increases depending on an increase in feed rate and spindle speed, but the influence of the feed rate is more dominant.…”
Section: Hole Cylindricity and Perpendicularity Analysismentioning
confidence: 96%
“…In drilling, perpendicularity is the deviation of the hole axis from the ideal cylinder axis with respect to the specified reference point. This geometrical defect reduces the load-bearing capacity of bolted joints causing stress concentration around hole edges [97,98]. The results show perpendicularity increases depending on an increase in feed rate and spindle speed, but the influence of the feed rate is more dominant.…”
Section: Hole Cylindricity and Perpendicularity Analysismentioning
confidence: 96%
“…The influence of a hole perpendicularity error on the performance of the composite mechanical joint is presented in ref. [84].…”
Section: Whqvlrq Frpsuhvvlrqmentioning
confidence: 99%
“…To minimize the unfavorable effects of perpendicularity error on the joints, increasing the bolt preload becomes an effective method. Further, Xu established a finite element model of composite double-nailed single-shear composites by combining the shear stress-strain relationship and stiffness discounting scheme (Xu, 2017). The load-carrying capacity and load distribution of the joint under different combinations of tilt angle and tilt direction were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of tilt direction on the bearing strength was not significant. Liu et al investigated the effect of hole perpendicularity error on the stress distribution of CFRP screwed joints and analyzed the relationship between the bolt preload and hole perpendicularity error through tests (Liu et al, 2018). It was concluded that the hole perpendicularity error resulted in stress concentration around the hole and nonuniform stress distribution in the joint region.…”
Section: Introductionmentioning
confidence: 99%